Trainee-led emergency laparotomy operating. Issue 10 (26th April 2020) - Boyd-Carson, H; Doleman, B; Lockwood, S; Williams, J P; Tierney, G M; Lund, J N
Abstract: Background: To achieve completion of training in general surgery, trainees are required to demonstrate competency in common procedures performed at emergency laparotomy. The aim of this study was to describe the patterns of trainee-led emergency laparotomy operating and the association between postoperative outcomes. Methods: Data on all patients who had an emergency laparotomy between December 2013 and November 2017 were extracted from the National Emergency Laparotomy Audit database. Patients were grouped by grade of operating surgeon: trainee (specialty registrar) or consultant (including post-Certificate of Completion of Training fellows). Trends in trainee operating by deanery, hospital size and time of day of surgery were investigated. Univariable and adjusted regression analyses were performed for the outcomes 90-day mortality and return to theatre, with analysis of patients in operative subgroups segmental colectomy, Hartmann's procedure, adhesiolysis and repair of perforated peptic ulcer disease. Results: The study cohort included 87 367 patients. The 90-day mortality rate was 15·1 per cent in the consultant group compared with 11·0 per cent in the trainee group. There were no increased odds of death by 90 days or of return to theatre across any of the operative groups when the operation was performed with a trainee listed as the most senior surgeon in theatre. Trainees were more likely to operate independently in high-volume centres (highest- versus lowest-volume centres: odds ratio (OR) 2·11, 95 per cent c.i. 1·91 to 2·33) and at night (00.00 to 07.59 versus 08.00 to 11.59 hours; OR 3·20, 2·95 to 3·48). Conclusion: There is significant variation in trainee-led operating in emergency laparotomy by geographical area, hospital size and by time of day. However, this does not appear to influence mortality or return to theatre. Graphical Abstract: This study showed significant variation in trainee-led operating in emergency laparotomy procedures by geographical area, hospital size and by time of day. However, this involvement in procedures required for Certificate of Completion of Training in general surgery did not appear to influence mortality or return to theatre in patients after adjustment for various preoperative features. Evidence that trainee-led operating is safe in selected cases